Historical Perspective: The Development of Critical Thinking in Indonesian ELT - Hamzah Puadi Ilyas (University of Muhammadiyah Prof. DR. HAMKA, 2017)
Even though critical thinking has been included in education system in Indonesia, it is unlikely to be widely implemented in teaching-learning processes in all levels of education in this country. Indonesian ELT (English Language Teaching) can actually play a role in promoting critical thinking in education. However, the development of ELT in this country since colonial to present era does not seem to facilitate students’ critical thinking skill. This article presents historical perspective with regard to ELT and critical thinking. The first part reviews the history of Indonesian education which did not promote critical thinking, followed by the historical development of Indonesian ELT. The third part discusses socio-political condition which could be partly solved by promoting critical thinking in education and society. The final part suggests incorporation of critical thinking into English textbooks as ELT can also be used as a vehicle for teaching critical thinking.